PELEPASAN INFORMASI REKAM MEDIS DALAM MENJAMIN ASPEK HUKUM KERAHASIAAN REKAM MEDIS DI PUSKESMAS TIRTAYASA - Heru Indra Cahya; Erwin Muhtaddin (Journal Of Applied Health Research And Development, 2022)
Background Medical Record according to Permenkes No.269/Menkes/Per/III/2008, Medical Record is a file that contains notes and documents about the patient's identity, examination results, treatment that has been given to the patient. Health facilities are responsible for protecting health information contained in medical records against possible loss, damage, falsification and unauthorized access. Maintaining information security, accuracy of information and ease of access to information are demands of health service organizations and health practitioners as well as authorized third parties. Meanwhile, parties who need information must always respect patient privacy. Overall, security, privacy, confidentiality and safety are devices that fortify information in medical records [1]. The purpose of this study was to determine the review of the release of medical record information in ensuring the legal aspects of the confidentiality of medical records at Kencana Hospital. Research method The research design used is descriptive research, which is a research method whose purpose is to present a complete picture of the social setting by describing a number of variables that are relevant to the problem and the unit under study among the phenomena being tested. This type of research is used to determine the process of providing medical record information and guaranteeing the legal aspects of medical record confidentiality at Kencana Hospital. The population in this study were all officers involved in the process of providing medical record information at Kencana Hospital which had 8 employees, which were divided into 3 medical record officers (1 head of medical records and 2 people served as distribution and retrieval officers), 2 people who handles related to insurance and 2 officers handles related to BPJS. In this study, the sample used was the party from the medical record unit, namely the medical record officer who has the authority in the process of providing patient medical information to a third party. The instruments used are Checklist Sheets and interview guidelines. In this study, the sampling used was purposive sampling technique because in sampling the authors considered certain things related to the research, The results of the research on Standard Operating Procedures related to providing patient medical information at the Kencana Hospital have an SOP. This SOP contains points for the process of releasing patient medical information, each point with a slightly different procedure depending on who the 3rd party is requesting. What is meant by 3rd parties here are patients, insurance companies, and legal institutions (courts). Each of these 3rd parties has made their respective procedures. The parties involved in the process of releasing patient medical information at Kencana Hospital are all medical record officers totaling 15 people (8 officers in the filing section), (2 people in the distribution of medical record files), and (5 people in the registration section). The information released is in the form of a photocopy of a medical resume sheet. At Kencana Hospital, the only party who can decide on the release of patient medical information is the medical record officer. Kencana Hospital does not yet have special security related to the process of releasing patient medical information, but if a patient is represented in the process of requesting release of information, the representative must have a power of attorney from the patient concerned. If the request for release of information is not represented, the patient will be given a release approval form from the medical record unit. Suggestion It is better to make Standard Operating Procedures related to the Release of Patient Medical Information referring to the Regulation of the Minister of Health of the Republic of Indonesia Number 36 of 2012 concerning Medical Secrets and Guidelines for the Implementation and Procedures of Indonesian Hospital Medical Records issued by the Director General of Yanmed.